Imagens que falam: a narrativa visual do cotidiano de jovens garotas estudantes de uma escola pública de São Carlos - SP - Redondo, Gabrieli Carolina (Universidade Federal de São Carlos)
This study is grounded in the understanding that the everyday lives of adolescents and young people are shaped by social markers such as gender, class, and territory. It is a qualitative, exploratory, and participatory research project aimed at understanding the daily experiences of young female students attending a public school. The Photovoice methodology was employed as a means of expression and analysis, combining image production with attentive listening and critical reflection. The investigation was conducted in a public school located on the outskirts of São Carlos, São Paulo, and involved female students who documented significant aspects of their daily routines through photographs, which were subsequently shared and discussed collectively among all participants. Data analysis was carried out using thematic analysis, allowing for the identification of emergent categories based on the participants’ oral and visual narratives. Group meetings enabled the collective construction of narratives based on the images, addressing themes such as self-esteem, self-care, family relationships, the burden of domestic tasks, aesthetic pressures, rivalry among girls, and future aspirations. The photographs and narratives revealed both challenges and potentials present in everyday life, with particular emphasis on affective bonds with female figures—especially mothers—as well as on the desire for recognition and belonging. Among the main challenges identified were gender inequality in domestic responsibilities, the need to reconcile academic demands with family caregiving, and pressures related to aesthetic standards. It is concluded that this research highlights the importance of recognizing the knowledge and experiences of young girls as a means of fostering more equitable and sensitive educational spaces. Furthermore, it contributes to the strengthening of social occupational therapy by demonstrating the potential of participatory methodologies to promote participation and to make visible experiences that are often silenced within school and broader social contexts.
Images that speak: the visual narrative of the daily life of young girls studying at a public school in São Carlos - SP
Keywords: Terapia Ocupacional; Juventudes; Gênero; Cotidiano; Photovoice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 5. Igualdade de Gênero